Reliability System Detection Of 1 Phase Network Short Detection Disorders - Daniel Tampubolon; Solly Aryza; Hamdani (Sean Institute, 2021)
In this study describes a circuit to detect the location of a fault line short 1 phase network. The single power supply that emits a voltage of 12 V will be converted into 2 voltage sources, namely voltage (+) and voltage (-). This voltage is used to supply a parallel resistance circuit which functions to find the difference in voltage to be measured. The difference in voltage is sent to the op amp. The op amp used is IC TL084 CN which has 4 op amps and only 1 op amp is used. After outputting the voltage from the op amp, it is sent to the interface (ADC). The signal emitted by the op amp is still an analog signal. While we use a PC that can only receive digital signals. So we need a series of interfaces (ADC) so that the PC can receive signals from the circuit. The cable used to send the signal uses an RS 232 cable or a serial USB cable. After the PC receives the signal via a serial USB cable, the signal is processed in Visual Basic 6.0. Before testing the tool, calibration is carried out first so that the resulting data results are more accurate which will be displayed in Visual Basic 6.0